Temporal and Spatial Characteristics of Precipitation in West River Basin Based on Remote Sensing Precipitation - QIN Zhanbo; FANG Rongjie; HUANG Guangling; SU Zhong; XU Jingxuan (Renmin Zhujiang)
To accurately analyze the spatial and temporal characteristics of precipitation in the West River Basin,this paper evaluates the applicability of GPM precipitation data in the West River Basin from 2001 to 2019 by the measured precipitation data from 34 meteorological stations in the basin and quantitatively analyzes the spatiotemporal variation characteristics of precipitation in the West River Basin based on the GPM data.The results show that the GPM data are consistent with the measured precipitation data with reasonable errors,and have applicability in the West River Basin.The annual precipitation in the basin shows an overall upward trend,and the characteristics of alternate stages of drought and flood periods.The precipitation from April to September accounts for 78.39% of the whole year.The spatial distribution of annual and monthly precipitation shows a gradually increasing trend from west to east step by step.The precipitation has increased in the past 19 years,but 72.39% of the areas do not reach the confidence level of 90%.The degree of precipitation variation is mainly moderate,accounting for 66.24%.In the past 19 years,78.50% of the areas have shown reverse continuous precipitation,and 61.16% of the areas where precipitation increased in the past 19 years do not reach the confidence level of 90%.The future precipitation is likely to reverse to a decreasing trend.The research results can provide theoretical support for scientific planning of West River Basin water resources and promoting the high-quality development of river basin water conservancy in the new stage.